What factors can support students' deep learning in the online environment: The mediating role of learning self-efficacy and positive academic emotions? - Zhao, Jingxian; Liu, Enyun (Frontiers in Psychology, 2022)
In 2020, the popularity of COVID-19 forced higher education institutions in many countries to turn to online distance learning. Therefore, the use of online education has become crucial in the world. However, this change of teaching mode has led to the decline of students' online learning quality and the problem that students can't conduct deep learning. Therefore, the current research aims at promoting deep learning in online environment, and constructs a theoretical model with learning self-efficacy and positive academic emotions as mediators, deep learning as dependent variable, perceived TPACK support, peer support, technical usefulness and ease of use as independent variables. The theoretical model was verified by SPSS26.0 and smartPLS3.0, and the conclusion was drawn: Positive academic emotions play a mediating role among perceived TPACK support and deep learning, perceived peer support and deep learning, perceived technology usefulness and ease of use and deep learning; Learning self-efficacy plays an mediating role among perceived TPACK support and deep learning, perceived peer support and deep learning, perceived technology usefulness and ease of use and deep learning. The current research conclusion fills the blank of the research on the theoretical model of deep learning in the online environment, and provides a theoretical basis for online teaching and learning quality practical improvement strategies.